Comparative climatology of outer tropical cyclone size using radial wind profiles - Albenis Pérez-Alarcón; Rogert Sorí; José C. Fernández-Alvarez; Raquel Nieto; Luis Gimeno (Weather and Climate Extremes, 2021)
In this study was performed a comparative climatology of outer tropical cyclone (TCs) size using radial wind profiles. A wind speed of 2 ms−1(∼4 kt) was taken as the threshold to define the TC size. The method proposed by Willoughby et al. (2006) (W06) to determine the wind profile showed the least variance and the smallest coefficient of variation of all profiles. W06 correctly described the radial wind structure of storms such as Hurricane Irma (2017) and Cyclone Giri (2010), compared with the European Centre for Medium-Range Weather Forecasts ERA-5 reanalysis data. Thus, W06 was used to develop the climatological TC size (TCSize) database. It was found that the tropical cyclones are largest when the maximum wind speed ranges between 20 and 40 ms−1and they most frequently reach a size between 700 and 800 km. The TCs exhibit their maximum size when they are in extratropical latitudes, while the smallest are observed in the low latitudes of both hemispheres. The global mean size is 748.7 km with a 95% confidence interval of [748.2,749.2] km. Median storm size is largest in the North Atlantic basin and smallest in the North Indian Ocean. The method proposed here is designed to be an objective metric that can be quickly applied to any TC when its position, maximum wind speed, and minimum central pressure are known. As a result, a TCSize database was created for all ocean basins, which could be useful for many applications, including different risk analyses.